Factors inhibiting the maturity and praxis of Made in Africa Evaluation - Takunda J. Chirau; Mokgophana Ramasobana (African Evaluation Journal, 2022)
This article documents critical factors inhibiting the deepening of the ‘Made in Africa Evaluation’ (MAE), both conceptually and practically. Monitoring and evaluation in Africa as a practice and discipline has been dominated by Global North perspectives. There have been efforts within the monitoring and evaluation space to build a practice and profession that is informed by epistemes and axiologies which are Afro-centric. The main stream approaches currently being used in African evaluations marginalize the African knowledge systems as well as African evaluators. Reconstructing and repositioning the value of Made in Africa Evaluation is a must, rather than a necessity.
This article documents critical factors inhibiting the deepening of the ‘Made in Africa Evaluation’ (MAE), both conceptually and practically. Monitoring and evaluation in Africa as a practice and discipline has been dominated by Global North perspectives. There have been efforts within the monitoring and evaluation space to build a practice and profession that is informed by epistemes and axiologies which are Afro-centric. The main stream approaches currently being used in African evaluations marginalize the African knowledge systems as well as African evaluators. Reconstructing and repositioning the value of Made in Africa Evaluation is a must, rather than a necessity.